Handbill advertisement for a production of Fidelio at Her Majesty's Theater, London, on July 2, 1864, conducted by Signor Arditi (London; United Kingdom, 2020)
Handbill advertisement for a production of Fidelio at Her Majesty's Theater, London, on July 2, 1864, conducted by Signor Arditi, with list of singers. Verso has an advertisement for Rimmel's Choice Perfumery and Elegant Novelties.